2020
DOI: 10.21203/rs.3.rs-40892/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of the COVID-19 Pandemic on Patients with Chronic Rheumatic Diseases: A Study in 15 Arab Countries

Abstract: Abstract Aim. To evaluate the impact of the Coronavirus Disease 2019 pandemic (COVID-19) on the access to rheumatology care for patients with chronic rheumatic diseases (CRD) in the Arab countries.Method. A web-based cross-sectional survey was designed by the Arab Adult Arthritis Awareness group (AAAA) consisting of 16 rheumatologists representing countries from the Arab League of Associations for Rheu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…Unsurprisingly, emerging literature supports our findings that individuals with RA experienced heightened feelings of fear, anxiety or stress during the pandemic compared to before 6,34–39 . In a survey of 361 respondents with rheumatologic conditions in the Bronx, the most affected borough of New York, USA, with a population disproportionately affected by COVID‐19, Maldonado et al 37 found that high levels of COVID‐related distress were reported.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Unsurprisingly, emerging literature supports our findings that individuals with RA experienced heightened feelings of fear, anxiety or stress during the pandemic compared to before 6,34–39 . In a survey of 361 respondents with rheumatologic conditions in the Bronx, the most affected borough of New York, USA, with a population disproportionately affected by COVID‐19, Maldonado et al 37 found that high levels of COVID‐related distress were reported.…”
Section: Discussionsupporting
confidence: 77%
“…It is also known that individuals using telehealth in the United States tend to have higher socioeconomic status with stable phone and internet services. 36,44 It is possible that remote consultations may widen present health inequalities, due to limited health literacy for example, which the limitations of our sample may not have identified. Our sample was recruited from selfcare intervention studies involving the use of technology and may be very unique.…”
Section: Consultations With Uk-based Patient Partnersmentioning
confidence: 98%
See 1 more Smart Citation
“…Currently, the COVID-19 pandemic leads to an urgent call for actions to mitigate the negative effects observed in several studies on psychological health, pain, and quality of life, as seen similarly in systemic autoimmune myopathies [57 ▪ ,61,62 ▪▪ ].…”
Section: Methodsmentioning
confidence: 99%
“…Patients with comorbidities are avoiding or delaying their care routines during the pandemic, which is placing them at a greater risk of developing complications. 6 Newer care delivery models in the form of remote healthcare platforms have been implemented in primary care clinics. PCTs assist in managing the health of such patients by contacting them via phone and through online video consultations.…”
Section: Ensuring Continuity Of Carementioning
confidence: 99%